Provenance of late-Quaternary sediments from Ross Sea region (Antarctica) - Matteo Perotti (Università degli Studi di Siena, 2018)
In this thesis the application of multi-disciplinary provenance methods to the study of late Quaternary sediments deposited along the edge of the continental shelf of Ross Sea and in the coastal area of McMurdo Sound (Southern Victoria Land) is treated. In particular, petrographic analysis of gravel fraction (clasts of different grain size) has been applied to glacimarine intervals related to the last advance and consequent retreat of the Antarctic Ice Sheet on the continental shelf at the Last Glacial Maximum. The sediments were analyzed using a petrographic approach, with logging and classification of gravel-sized clasts of various lithologies in cores distributed along an E-W transect along the entire Ross Embayment. The classification and quantitative approach applied on the gravel fraction, coupled with geo and thermo- chronological techniques on sandy fractions from the same stratigraphic intervals, allowed to refine the existing data in the region dealing with drainage pattern of paleo-ice flows during the Last Glacial Maximum. In particular, in the region of Eastern Ross Sea, the acquired new data allowed to better constrain the contribution of West Antarctica Ice Sheet to the ice drainage in the Ross Embayment, while in the Central and Western Ross Sea the contribution of East Antarctic Ice Sheet has been revealed by new petrographic data that have qualitatively refined existing provenance models. In addition, a petrographic approach on onshore unconsolidated sediments (Ross Sea Drift) transported by a grounded Ice Sheet in the McMurdo Sound region (Southern Victoria Land) has been carried out, applying a quantitative approach to various granulometric fractions. Deposits have been classified according to thelithological composition of clasts that composed these sediments. The data obtained allowed to refine the existing ice transport models in the region and to hypothesize paleo ice flow depending on the provenance of glacial erratics.